E-Module for Preserving the Local Wisdom of Sidoarjo City among Generation Alpha in Elementary Schools - Norita Boru Sagala; M. Bambang Edi Siswanto; Nurul Istiq'faroh; Naffi Isbadrianingtyas (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
The development of digital technology in the Society 5.0 era has had a major impact on the learning patterns of Generation Alpha in elementary schools. Generation Alpha is a group of children who grew up side by side with digital technology, thus requiring innovative, interactive, and contextual learning media. Therefore, teachers are required to be able to develop teaching modules that are adaptive to these technological developments. This study aims to develop an e-module containing the local wisdom of the traditional culinary